PERCUTANEOUS TRANSLUMINAL ANGIOPLASTY IN CHRONIC KIDNEY DISEASE PATIENTS WITH CENTRAL VEIN STENOSIS POST HEMODIALYSIS CATHETER IMPLANTATION - darwis, iswandi; hariawan, hariadi; ismail, muhammad taufik (Fakultas Kedokteran, 2025)
Background. The use of central venous catheters as temporary vascular access is found in 20% of CKD patients undergoing routine hemodialysis. Apart from having benefits, the use of a central venous catheter also has risks. One of the complications of using a central venous catheter is central venous stenosis. Central vein stenosis is associated with the placement of a subclavian catheter as a hemodialysis access. Case Report. Three cases of central venous stenosis after placement of a hemodialysis catheter in the subclavian vein were reported. Complaints of swelling on the side where the hemodialysis catheter is inserted are felt 1-2 months after removing the hemodialysis catheter. Apart from that, a complaint that often arises is that there are obstacles to the flow during the hemodialysis process. The subclavian vein is a common site for hemodialysis catheter implantation, but the incidence of central vein stenosis is consistent with these three patient cases. Doppler ultrasonography is the initial examination and is important for detecting central vein stenosis even though it cannot make a definitive diagnosis. Venography and Digital Subtraction Angiography examinations are the gold standard examinations for confirming central vein stenosis. These three patients were found to have stenosis and total occlusion of the central vein. The patient underwent percutaneous transluminal angioplasty but the vein patency was still low so a stent was placed. To prevent intrastent stenosis, antiplatelets are given for life. The patient underwent an evaluation after stent installation and found clinical improvement in the form of reduced swelling. Conclusion. Central venous stenosis that occurs in patients with chronic kidney disease due to complications after installing temporary access for hemodialysis using a central venous catheter is effective for percutaneous transluminal angioplasty and stent installation.